CLAUSE ANALYSIS BASED ON THE PRESENCE AND ORDER OF FUNCTIONS IN SURAH AR-RAHMAN - Syammary, Naufal Akmal; Firmansyah, Haris Furkon Hasbi; Salsabila, Fithri (Proceeding of International Conference of Islamic Education, 2024)
In linguistic analysis, an understanding of clauses is essential to uncovering the meaning and structure of language. One of the main approaches in this analysis is to pay attention to the presence and sequence of functors in the clause. This article aims to analyze the clauses based on the presence and sequence of functors in Surat Ar-Rahman. This study used a qualitative descriptive analysis approach. This analysis involves recognizing the position of each word and element in a sentence as well as how they are connected to each other in conveying meaning. Based on the results of data analysis, it was found that there are five forms of clause patterns in Surat Ar-Rahman, namely: 1) one fungtor clause pattern S and P, 2) two fungtor clause patterns S, P, and O, 3) one fungtor clause pattern P and O, 4) one fungtor clause pattern P and K, and 5) one fungtor clause pattern P,  O, & K.